The Study of In-Migration between Provinces in Indonesia by Panel Data Regression - Asmadhini Handayani Rahmah (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2016)
Indonesia has 34 provinces. There are many peoples spread out across Indonesia and the vast area owned makes Indonesia become one of the biggest 4 (four) most population country in the world. However, the population density is not spread evenly in Indonesia. This has become interesting to be observed how the distribution of population in Indonesia by using variable in-migration as a dependent variable that is assumed to be influenced by four (4) independent variables. Thoseindependent variables are the Gross Domestic Product (GDP), the Regional Minimum Wage, Unemployment Rate (TPT) and Labor Force Participation Rate (LFPR). Data is collected fromwww.BPS.go.id . The analysistool used panel data regression, denote a data type is a combination of time series data (time series) and cross section data. The best selected model used in this research is Fixed Effect model to obtain 33 models for 33 provinces. The variables that influence the inmigration is the Open unemployment rate (TPT), which has a negative correlation to in-migration, while the Labor Force Participation Rate (LFPR) has a positive correlation.